2015
DOI: 10.4103/2229-5178.171052
|View full text |Cite
|
Sign up to set email alerts
|

Pyodermatitis vegetans after total colectomy

Abstract: Pyostomatitis–pyodermatitis vegetans (PPV) is a rare dermatological manifestation of inflammatory bowel disease, characterized by erythematous, vesiculopustular, exudative, annular, and/or vegetating plaques over the intertriginous regions that may precede or appear at the same time as the mucosal lesions. Systemic corticosteroids, dapsone, sulfasalazine, azathioprine, cyclosporine, and subtotal/total colectomy are the most common treatment options. A 16-year-old male patient presented to our outpatient clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Multiple previous studies have considered PDV as a clinical marker for IBD activity and recommended that a total/subtotal colectomy is a therapeutic option for complete remission of symptoms 3 , 6 , 13 . However, in 2015, Uzunçakmak et al 9 reported on a case of PDV developed shortly after a total colectomy and discontinuation of systemic corticosteroid 9 . Here we report a first presentation of PDV 3 years after total colectomy in a patient with Crohn's disease.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Multiple previous studies have considered PDV as a clinical marker for IBD activity and recommended that a total/subtotal colectomy is a therapeutic option for complete remission of symptoms 3 , 6 , 13 . However, in 2015, Uzunçakmak et al 9 reported on a case of PDV developed shortly after a total colectomy and discontinuation of systemic corticosteroid 9 . Here we report a first presentation of PDV 3 years after total colectomy in a patient with Crohn's disease.…”
Section: Discussionmentioning
confidence: 69%
“…Previous reports have indicated that PDV is frequently associated with IBD in 70% of cases, and up to 100% in a recent cohort study 1, 2, 3, 4 , 6 , 8 . PDV commonly affects adults in the third decade of life with a male/female ratio of 3:1 3 , 9 . The etiology of PDV is still unknown.…”
Section: Discussionmentioning
confidence: 98%
“…They are used as systemic, intralesional, and topical treatments depending on disease severity. All the cases reviewed that used corticosteroids achieved clearance, however relapse was common when tapering [1][2][3][4][6][7][8][9][10][11][12][13]. Other systemic treatments for PPV include dapsone, azithromycin,…”
Section: Discussionmentioning
confidence: 99%